The impact of annual earnings announcement on share returns / Chali Awang @ Abdul Hakam - Awang @ Abdul Hakam, Chali (1995)
The objective of this study is to examine the impact of the informational content of annual earnings's announcement on share returns. In addition, this study also explores whether the Annual Earnings Announcement have informational content which effect the share returns.